2010
DOI: 10.1158/1940-6207.capr-09-0050
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Unified Mechanism for the Reduction of Human Breast Cancer Risk by the Hormones of Pregnancy

Abstract: Parity in women is associated with reduced lifetime risk of breast cancer, and hormones of pregnancy [estrogen (E), progesterone (P), human chorionic gonadotropin (hCG)] are implicated. Parity also reduces mammary cancer risk in carcinogen-exposed rats, and administering pregnancy hormones to these animals is similarly effective. Because pregnancy hormones are also able to stimulate cancer growth, we proposed to resolve this dichotomy by determining whether administered pregnancy hormones elicit the cancer-inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…In addition to hCG, other pregnancy hormones are believed to plan an important role in the protection conferred by pregnancy on maternal breast cancer risk. Studies have shown that α-fetoprotein (AFP) may also have a protective effect on maternal breast cancer risk [30]. AFP binds to estradiol and prevents estrogen-dependent growth of breast cancer cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hCG, other pregnancy hormones are believed to plan an important role in the protection conferred by pregnancy on maternal breast cancer risk. Studies have shown that α-fetoprotein (AFP) may also have a protective effect on maternal breast cancer risk [30]. AFP binds to estradiol and prevents estrogen-dependent growth of breast cancer cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…AFPep was derived from the naturally occurring protein α-fetoprotein (AFP) [16, 29, 30] which is produced during fetal development [4, 5, 21] and which exhibits anti-oncogenic activity [23]. AFP is reported to be the primary agent responsible for a decreased incidence of breast cancer in populations of women who have experienced a full-term pregnancy compared to the nulliparous population [22, 24, 37].…”
Section: Discussionmentioning
confidence: 99%
“…The pregnancy-based epidemiologic considerations of the effect of AFP in breast cancer, together with the laboratory and clinical observations that AFP has activity against cancer (and especially breast cancer), were brought together to call attention to the centrality of AFP as an anticancer protein (42). Over the years, investigators had proposed various hormones of pregnancy (e.g., estradiol, estriol, androstendione, testosterone, progesterone, chorionic gonadotropins) as the agent responsible for the pregnancy-associated reduction in risk of breast cancer later in life.…”
Section: Laboratory Observationsmentioning
confidence: 99%
“…Seemingly, a number of different pregnancy-associated endocrine substances are effective surrogates for parity in terms of reducing mammary cancer risk, but there had been no reasonable explanation of why these diverse treatments should lead to the same outcome. Jacobson and colleagues (42) repeated the studies of the earlier investigators, duplicating their methods of treating carcinogen-exposed rats with estradiol plus progesterone, estriol plus progesterone, estriol alone, or chorionic gonadotropin. In each case, serum levels of AFP were elevated as a result of exposure to the various hormones of pregnancy while tumor incidence decreased.…”
Section: Laboratory Observationsmentioning
confidence: 99%
See 1 more Smart Citation